Assessing the usage of game-based learning in public sector accounting class: feedback from students / Intan Marzita Saidon ... [et al.] - Saidon, Intan Marzita; Che Salleh, Saluana; Ab Ghani, Nadzri (2019)
The aim of this extended abstract is to share feedback given by students during a pilot test to assess an innovative game-based learning created for the Public Sector Accounting course. Public Sector or Government Accounting is one of the elective courses offered for the degree of accountancy students. Past academic records revealed that most students failed to gain excellent results for this course. The pivotal reason is due to the fact that this course requires students to have good comprehension and memorizing skills. In short, students need to read, understand and memorize important facts. Acknowledging the difficulties faced by students in mastering these skills, Government Accounting Visual Interactive Game (GAVIG) was innovated with the aim to provide an alternative way in learning this course. GAVIG is an innovative game-based learning device which integrates visual and interactive aspects and provides a new learning experience for students.